2019
DOI: 10.1002/cmdc.201800805
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of the Dinuclear Trithiolato‐Bridged Arene Ruthenium Complex Diruthenium‐1 in an Apoferritin Nanocage: Structure and Cytotoxicity

Abstract: The effects of encapsulating the cytotoxic dinuclear trithiolato‐bridged arene ruthenium complex [(η6‐p‐MeC6H4iPr)2Ru2(μ2‐S‐p‐C6H4tBu)3]Cl (DiRu‐1) within the apoferritin (AFt) nanocage were investigated. The DiRu‐1‐AFt nanocarrier was characterized by UV/Vis spectroscopy, ICP‐MS, CD and X‐ray crystallography. In contrast to previously reported Au‐ and Pt‐based drug‐loaded AFt carriers, we found no evidence of direct interactions between DiRu‐1 and AFt. DiRu‐1‐AFt is cytotoxic toward immortalized murine BALB/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…Since more than one molecule of AP-1 per AFt chain is present, analysis of the protein structure points out that there are a lot of free AP-1 molecules trapped within the bulk. Similar results were found for other metallodrug-encapsulated Ft systems [40][41][42]. These molecules are responsible for the biological activity of the nanocomposite.…”
Section: Discussionsupporting
confidence: 85%
“…Since more than one molecule of AP-1 per AFt chain is present, analysis of the protein structure points out that there are a lot of free AP-1 molecules trapped within the bulk. Similar results were found for other metallodrug-encapsulated Ft systems [40][41][42]. These molecules are responsible for the biological activity of the nanocomposite.…”
Section: Discussionsupporting
confidence: 85%
“…The cell experiments showed that ferritin-cisplatin NPs could inhibit the growth of tumor cells slowly and continuously, and enhance the cell absorption of cisplatin [55,123]. Similar to cisplatin, alternative metal compounds based on Ru and Au have been prepared and evaluated for their cytotoxic activity in recent years, mostly by Merlino and co-workers [89,[92][93][94][95]. The adducts of these compounds with ferritin are less toxic than free drugs and are moderately selective towards cancer cells compared with non-malignant cells [80].…”
Section: Applications In Medicine and Diagnosticsmentioning
confidence: 99%
“…However, passive diffusion of some metallic compounds into apoferritin turned out to be unfavorable, attributed to the limited pore size of the cage shell. Therefore, many metallodrugs including cisplatin [ 55 ], Auoxo3 [ 92 ], Auoxo4, Au2phen [ 93 ], 4-PF6 [ 94 ], Di-Ruthenium-1 [ 95 ], [Ru(bpy) 2 dppz] 2+ , [Ru(phen) 2 dppz] 2+ , and [Ru(bpy) 3 ] 2+ [ 96 ] have been encapsulated into ferritin cage through biomineralization coupled with pH-induced disassembly and reassembly. The binding efficiency depends on the metal ion, ferritin species, and preparation conditions.…”
Section: Preparation Of Ferritin-hybrid Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, only a few examples concerning the encapsulation of Ru( ii ) compounds into ferritin nanocages, accomplished by the pH assisted method, have been reported so far. Merlino and coworkers 37 encapsulated up to 36 molecules of [(h 6 - p -MeC 6 H 4 iPr) 2 Ru 2 (m 2 -S- p -C 6 H 4 t Bu) 3 ]Cl per ferritin cage whereas the hydrophobic [Ru(bpy) 3 ] 2+ , [Ru(bpy) 2 dppz] 2+ and [Ru(phen) 2 dppz] 2+ compounds reported by Feng et al 30 were loaded in a ratio between 7–40 molecules per ferritin cage. However, all these studies referred to horse-spleen ferritin.…”
Section: Resultsmentioning
confidence: 99%